Nazhir Profesional Kunci Kesuksesan Wakaf Produktif - Ridwan, Murtadho (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2012)
Nazhir in waqf activities does not constitute as one of its principles (rukn). But, in its execution or implementation of asset management, Nazhir has a central role. The development and decrease of waqf assets management depends on Nazhir. Nazhir has a strategic position and function in the management and development of waqf, therefore, the role of Nazhir is really needed anytime and anywhere. However nowadays there are many Nazhir that can not manage waqf well so a problem of consumptive waqf arises. To solve the problem; consumptive waqf should be changed to productive waqf, individual Nazhir should be changed to institutional Nazhir and traditional Nazhir should be changed to professional Nazhir. Actually professional Nazhir has an obligation to manage and maintain the waqf property. Professional Nazhir that recruited must have the ability of Islamic law, waqf law and modern business management. Thus Nazhir will be able to carry out its duties and obligation in managing waqf optimally in accordance with the expectations of Wakif. In conclusion professional Nazhir must have the capability of: human skill, human technical and human relation